Population pharmacokinetic analysis of RO5459072, a low water‐soluble drug exhibiting complex food–drug interactions. Issue 9 (10th March 2021) - Kratochwil, Nicole A.; Stillhart, Cordula; Diack, Cheikh; Nagel, Sandra; Al Kotbi, Nada; Frey, Nicolas
Abstract : Aims: RO5459072, a cathepsin‐S inhibitor, Biopharmaceutics Classification System class 2 and P‐glycoprotein substrate, exhibited complex, nonlinear pharmacokinetics (PK) while fasted that seemed to impact both the absorption and the disposition phases. When given with food, all nonlinearities disappeared. Physiologically based PK (PBPK) modelling attributed those nonlinearities to dose‐dependent solubilisation and colonic absorption. The objective of this population PK analysis was to complement the PBPK analysis. Methods: PK profiles in 39 healthy volunteers after first oral dosing (1–600 mg) while fasted or fed in single and multiple ascending dose studies were analysed using population compartmental modelling. Results: The PK of RO5459072 while fed was characterized by a 1‐compartmental PK model with linear absorption and elimination. The nonlinearities while fasted were captured using dose dependent bioavailability and 2 sequential first‐order absorption phases: one following drug administration and one occurring 11 hours later and only for doses >10 mg. The bioavailability in the first absorption phase increased between 1 and 10 mg and then decreased with dose, in agreement with in vitro dissolution and solubility studies. The remaining fraction of doses to be absorbed by the second absorption phase was found to have a bioavailability similar to that in the first absorption phase. Conclusion: The population PK model supported that dissolution‐ and solubility‐limited absorption from the proximal and distal intestine alone explains the nonlinear PK of RO5459072 in fasted state and the linear PK in fed state. This work, together with the PBPK analysis, raised our confidence in the understanding of this complex PK.